Activating JAK1 mutation may predict the sensitivity of JAK-STAT inhibition in hepatocellular carcinoma - Yang, Shuqun (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is the fifth most common type of cancers worldwide. However, current therapeutic approaches for this epidemic disease are limited, and its 5-year survival rate hasn't been improved in the past decades. Patient-derived xenograft (PDX) tumor models have become an excellent in vivo system for understanding of disease biology and drug discovery. In order to identify new therapeutic targets for HCC, whole-exome sequencing (WES) was performed on more than 60 HCC PDX models. Among them, four models exhibited protein-altering mutations in JAK1 (Janus Kinase 1) gene. To explore the transforming capability, these mutations were then introduced into HEK293FT and Ba/F3 cells. The results demonstrated that JAK1(S703I) mutation was able to activate JAK-STAT (Signal Transducer and Activator of Transcription) signaling pathway and drive cell proliferation in the absence of cytokine stimulation in vitro. Furthermore, the sensitivity to the treatment of a JAK1/2 inhibitor, ruxolitinib, was observed in JAK1(S703I) mutant PDX model, but not in other non-activating mutant or wild type models. Pharmacodynamic analysis showed that phosphorylation of STAT3 in the Ruxolitinib-treated tumor tissues was significantly suppressed. Collectively, our results suggested that JAK1(S703I) is an activating mutation for JAK-STAT signaling pathway in vitro and in vivo, and JAK-STAT pathway might represent a new therapeutic approach for HCC treatment. Monotherapy using a more potent and specific JAK1 inhibitor and combinatory therapy should be further explored in JAK1 mutant PDX models.